The Influence Of Learning Process Quality And Learning Motivation On Student Learning Achievement - Suparti, Hana; Daliman, Muner (Technium Social Sciences Journal, 2023)
The influence of the teaching and learning quality process affects the improvement of student learning outcomes in addition to the selection of inputs, there are also other factors that determine the so-called external factors and students’ internal factors. External factors of students include school infrastructure, teachers, learning processes and other factors that come from the family environment. While internal factors, including health, intelligence, talent, interests, motivation and so on. The influence of the quality of the learning process is a very important factor in determining student learning outcomes. Meanwhile, motivation is a factor to generate, underlie, and direct students’ learning actions. The purposes of this study are: 1) To determine the effect of the quality of the learning process and learning motivation on student achievement partially. 2) To determine the effect of learning motivation on student achievement